A dinâmica urbana em Araguari e Ituiutaba /MG sob a ótica do sistema de trânsito e transporte - Gouveia, Camilla Ferreira (2013)
Abstract This Project treats the urban dynamic from the perspective of the transit system and transportation in two cities of Triangulo Mineiro - Ituiutaba/MG and Araguari/MG. During this research to understand how the displacement occurs the population in the context of cities and which circumstances motivate the preferences of each citizen in the use of means of transport. In fact, the objective of this project is discuss the organization of the urban space and the relationships between the various agents of transit, such as motorcyclists, cyclists, pedestrians, motorists of private cars and transportation users public by bus and pointing suggestions of a reorganization Urban guided in the use of public transportation by bus and use of non-motorized modes such as cycling. To this, utilized-are three methodological processes, being that the first refers to bibliographical researches that based the aportes theorists discussed, the second in turn, covered the implementation of questionnaires and field researches in the two cities studied and the third consists in analysis of data collected in the previous step subsequent writing of the paper. From the studies can-if realize that in cities analyzed the urban system transit and transportation presents deficits regarding the urban mobility quality, ie, in Ituiutaba and Araguari car use particular is intense and lack of public policies in respect the use of the bus and the modal non-motorized further contributes to the lag of the same. It is observed that the bus lines and fleets are insufficient in the face of potential demand of the cities studied, moreover it emphasizes the intense use of motorcycle taxis by these populations, especially regarding sporadic use. In the case of bicycles, it is observed that in Araguari Ituiutaba and the use of these heavy although there is one policy for the use of the same, there cycle paths or lanes that allow the rider to secure traffic. At the end of the work from experiences in other cities of Brazil, was discussed proposals for interventions on the dynamics in urban transit systems and transportation of cities studied in order to improve urban mobility.